2018
DOI: 10.3389/fimmu.2018.01604
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Stimulates Nicotinic Acetylcholine Receptors to Control ATP-Mediated Monocytic Inflammasome Activation

Abstract: Blood levels of the acute phase reactant C-reactive protein (CRP) are frequently measured as a clinical marker for inflammation, but the biological functions of CRP are still controversial. CRP is a phosphocholine (PC)-binding pentraxin, mainly produced in the liver in response to elevated levels of interleukin-1β (IL-1β) and of the IL-1β-dependent cytokine IL-6. While both cytokines play important roles in host defense, excessive systemic IL-1β levels can cause life-threatening diseases such as trauma-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 67 publications
7
63
2
Order By: Relevance
“…For example, activation of nAChR in monocytes inhibits ATP-induced inflammasome activation by inhibiting IL1β-release. 14,51,52 In conclusion, the present findings reveal that the whole transcriptome of tracheal epithelial BC is distinct to that | 331 HOLLENHORST ET aL. of ciliated cells.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…For example, activation of nAChR in monocytes inhibits ATP-induced inflammasome activation by inhibiting IL1β-release. 14,51,52 In conclusion, the present findings reveal that the whole transcriptome of tracheal epithelial BC is distinct to that | 331 HOLLENHORST ET aL. of ciliated cells.…”
mentioning
confidence: 52%
“…In our study the acute inhibition of M2R in the trachea almost doubled the increase in PTS after stimulation of brush cells with bitter tasting substances. 14,51,52 In conclusion, the present findings reveal that the whole transcriptome of tracheal epithelial BC is distinct to that | 331 HOLLENHORST ET aL. 16 Additionally, ACh mediates important innate immune functions after being released from BC, for example, induction of protective respiratory reflexes.…”
mentioning
confidence: 67%
“…[V11L, V16D]ArIB and RgIA4 were produced and characterized as described previously [ 5 , 7 , 43 , 44 , 45 ]. Concentrations of all compounds used in this study were optimized in previous experiments on human monocytic U937 cells [ 6 , 7 , 8 , 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, PC is a ligand of the pentraxin C-reactive protein (CRP), an acute phase protein present in human blood that is a widely used clinical marker for inflammation [ 9 , 10 ]. We found that endogenous CRP-PC complexes are potent nAChR agonists that also inhibit the ATP-dependent inflammasome assembly and IL-1β release by human monocytic cells, whereas PC-free CRP is ineffective [ 11 ]. Moreover, we discovered that dipalmitoyl phosphatidylcholine (DPPC) and metabolites of phosphatidylcholines such as lysophosphatidylcholine or glycerophosphocholine (GPC) also function as nAChR agonists [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inversely, the expansion may limit excessive cell damage during inflammation. In humans, the acute phase protein CRP contains inflammation as part of a negative feedback loop [135]. Thus, the round goby may re-enter homeostasis faster compared to other fish species with smaller CRP/APCS repertoires.…”
Section: Response To the Environmentmentioning
confidence: 99%